Oppositions and Antinomies of Modern Educational Reality - V. P. Ignatiev (Высшее образование в России)
The article reveals some unresolved issues concerning the processes of planning, organizing, conducting and evaluating university education in modern conditions. The purpose of the study is to clarify what oppositions are currently being maintained, and what needs to be done to address problematic situations. Among the oppositions identified by the author, there are oppositions between the standardization and unification of education, which are opposed by the autonomy of universities and the individualization of the learning process; between thread-group organization of educational process, characteristic of the traditional system of higher education, and building of individual educational trajectory; between pedagogue-centered and student-centered paradigms of higher education; between the traditional system of education (teaching) and electronic learning (e-learning), between the old system of assessing students based on the exams in specific disciplines, and the need to determine the level of formation of competences; between academic and scientific models ofpostgraduate school.The following research methods were implemented: a theoretical method (analysis of scientific literature, legislative and normative documents, teaching materials, internal local acts relating to the organization of the educational activities of the University), interpretation (comprehensive and systematic study of the object of study, comparing different objects of study among themselves, summarizing their theoretical and practical experience, etc.). In the study, based on the identified oppositions in the organization of the educational process at the University - standardization and unification of education, the conclusions were made about the need for thorough and comprehensive analysis of the existing management system of higher education and suggestions for its improvement and bringing into line not only with the requirements of legislative and normative documents regulating activity of the Russian universities, but also taking into account the interests of all the stakeholders interested in the learning outcomes and the preparation of competitive specialists.